(untitled) - Winograd, Morley (New Brunswick, NJ, 2011)
Millennial Momentum, Winograd and Hais investigate how the beliefs and practices of the Millennials are transforming other areas of American culture, from education to entertainment, from the workplace to the home, and from business to politics and government. The Millennials’ cooperative ethic and can-do spirit have only just begun to make their mark, and are likely to continue to reshape American values for decades to come.
Keywords: Tham gia chính trị,Political participation; Dwellings; Hoa Kỳ,United States